Answer:
x = 2
Explanation:
Solve for x:
12 - 3 x = 6
Hint: | Isolate terms with x to the left hand side.
Subtract 12 from both sides:
(12 - 12) - 3 x = 6 - 12
Hint: | Look for the difference of two identical terms.
12 - 12 = 0:
-3 x = 6 - 12
Hint: | Evaluate 6 - 12.
6 - 12 = -6:
-3 x = -6
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of -3 x = -6 by -3:
(-3 x)/(-3) = (-6)/(-3)
Hint: | Any nonzero number divided by itself is one.
(-3)/(-3) = 1:
x = (-6)/(-3)
Hint: | Reduce (-6)/(-3) to lowest terms. Start by finding the GCD of -6 and -3.
The gcd of -6 and -3 is -3, so (-6)/(-3) = (-3×2)/(-3×1) = (-3)/(-3)×2 = 2:
Answer: x = 2